Shear Strength of Carbon Fiber Reinforced Concrete Without Transverse Reinforcement - جحجاح غاندي; أصلان طارق; غالية رامية (Latakia University Journal -Engineering Sciences Series, 2020)
A couple of Decades ago research began in different laboratories in the world about the material of fiber reinforced concrete: glass, plastic, steel, carbon, with a view to its use in civil construction, fibers increase the resistance of the concrete on pressure and tensile but the primary role of it lies in improving concrete behavior and converting it from brittle to plastic. beams are subjected to effect of bending moment and shear strength, It is necessary to present an adequate resist to shear strength, to avoid the happening of any kind of the sudden shear failure. Several studies have recently been conducted to improve the shear strength of concrete beams, Some included add fibers(steel, glass and carbon)to concrete. This research present an experimental and analytical study for adding carbon fibers to the concrete of non-reinforced beams on shear in order to estimate the effect of its on shear strengthof concrete beams. Fifteen concrete beams were tested at different volume fraction of carbon fibers ranging from (0.00-0.25-0.5-0.75-1)%, in groups containing 3 similar beams. The addition of carbon fibers increased the loads causing the first moment crack by (20-30)% and the loads causing the first shear crack by (16.7-33.3)% as well as the failure load by (10.8-32.3)% compared to the non-fiber reinforced beam. There was good agreement were between experimental and analytical results at all loading stages.